Current research progress on the viral immune evasion mechanisms of African swine fever virus - Changjiang Weng (BMC, 2024)
Abstract African swine fever (ASF), caused by the ASF virus (ASFV), is an acute, severe, and highly contagious infectious disease in domestic pigs and wild boars. Domestic pigs infected with a virulent ASFV strain can have morbidity and mortality rates of up to 100%. The epidemic of ASF has caused serious economic losses to the global pig industry. Currently, there is no safe and effective vaccine or specific drug for treating ASF. Therefore, ASFV still poses a great threat to pig factories. ASFV is a double-stranded DNA virus with a complex icosahedral multilayer structure. The ASFV genome contains 150-170 open reading frames (ORFs) that encode 150-200 proteins. Some ASFV-encoded proteins are involved in virus invasion, genome replication, DNA repair, and virion formation. Some ASFV proteins execute immunomodulatory functions by regulating the host antiviral innate immune response. Accumulating studies have shown that the immunomodulatory functions of ASFV genes are closely related to the virulence and pathogenicity of ASFV isolates. This review summarizes the research advances on ASFV immune evasion mechanisms in African swine fever patients and provides new insights for developing attenuated live vaccine candidates to prevent and control ASF.